The Haskins Society journal, Volume 18, 2006 studies in Medieval history - Morillo, Stephen 1958-; Korngiebel, Diane (The Boydell Press, 2023)
Fruits of the most recent research on the worlds of the eleventh and twelfth centuries are presented in this collection. It features several articles on textual criticism with important revisions to controversial texts and their readings, as well as pieces on cultural history, an investigation into monetary history, and analyses of the legal and political mechanisms of conquest